THE GEOLOGY AND STRUCTURAL POSITION OF AYGEDZOR ORE KNOT (Proceedings of the YSU C: Geological and Geographical Sciences, 2001)
In the article the structural condition of localization of golden, molibdenium and copper-molibdenium mineralization in the area are examined. The role of the disjunctive fractures, which are conjugated with Debacly fault, in the distribution of mineralization is elucidated. With the purpose of revealing new long-range territories a detailed geostructural analysis of 2-3 km width zone adjacent to Debacly fault is given.
Keywords: Аygedzor ore knot; Debacly fault; golden; molibdenium; copper-molibdenium mineralization; disjunctive fractures